Teaching Methods used by Professional EFL Teachers of High School Level in Makassar - Baso jabu; Chairil Anwar Korompot (Seminar Nasional LP2M UNM, 2017)
The objective of the research is to describe the teachers’ concept of good teaching methods, kinds of teaching methods used by professional EFL teachers, and the reasons of the professional EFL teachers used the methods. The data sources for the research are three professional EFL teachers from three high school level in Makassar. This research employed qualitative approach with a grounded theory method for the research. The researchers act as the main instrument, using field notes, audio and video recorders. In the data collection, the researchers conducted interview and direct classroom observation. In analyzing the data, the researchers employed coding method that comprised three steps, open coding, axial coding, and selective coding. The result of the research shows that the three subjects have different statements about teaching methods, but their concept is basically in line with the theories about teaching method proposed by the experts. They stated that the teaching method is a set of principles, procedures or strategies to be implemented by teachers to achieve desired learning in students. During their teaching the teachers used PPP (presentation, practice and production) method, communicative approach, discussion method, task-based learning, audio lingual method, and ESA (engage, study, and activate) method. The three research subjects suggest similar points considered by teachers in choosing a teaching method to be applied in the classroom. To choose a method the most important things to consider are the material and the students learning style